Seidenfia manikathila (Orchidaceae, Epidendroideae, Malaxideae), a new species from south Western Ghats, India - Mathew, Jose; Pichan, Salim; Madhavan, Radhamany; Sarojini, Usha Soman; Madhusudhanan, Karadka; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2021)
Seidenfia manikathila J.Mathew, P.M. Salim & Szlach. (Orchidaceae), a new species from the southern Western Ghats, Kerala, India, is described and illustrated based on morphological data. We demonstrate that the new species differs from other Seidenfia species both in vegetative and floral characters. The diagnostic morphological characters, distribution and images of the new species are presented in this paper. Images and key to the known species of Seidenfia coming under the section Seidenfia from India (S. densiflora, S. intermedia, S. malabarica, S. rheedi, S. versicolor) is also provided.